1985
DOI: 10.1159/000183480
|View full text |Cite
|
Sign up to set email alerts
|

Serum Phosphate, Parathyroid Hormone and Vitamin D Metabolites in Patients with Chronic Renal Failure: Effect of Aluminum Hydroxide Administration

Abstract: Patients with chronic renal failure showed the existence of phosphate retention, secondary hyperparathyroidism, and reduced production of 1,25-(OH)2D. In order to determine the effect of correction of hyperphosphatemia on secondary hyperparathyroidism and vitamin D metabolism in those patients, 7 nondiaiyzed patients with chronic renal failure were treated with large doses of Al(OH)3 (15–18 g/day) to correct their high levels of serum phosphate. After treatment with A1(OH)3, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In the early 1970s it was demonstrated that anephric rats that received 3 H-25(OH)D 3 had no detectable amounts of 3 H-1,25(OH) 2 D 3 in their circulation (1,26). This was confirmed by the observation that patients with CKD had little if any detectable levels of 1,25(OH) 2 D in their circulation (2,26,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). Thus it has always been assumed that the kidney is the sole source for the production of 1,25(OH) 2 D 3.…”
Section: Extra Renal Production Of 125(oh) 2 D 3 and Its Role In Canmentioning
confidence: 84%
See 2 more Smart Citations
“…In the early 1970s it was demonstrated that anephric rats that received 3 H-25(OH)D 3 had no detectable amounts of 3 H-1,25(OH) 2 D 3 in their circulation (1,26). This was confirmed by the observation that patients with CKD had little if any detectable levels of 1,25(OH) 2 D in their circulation (2,26,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). Thus it has always been assumed that the kidney is the sole source for the production of 1,25(OH) 2 D 3.…”
Section: Extra Renal Production Of 125(oh) 2 D 3 and Its Role In Canmentioning
confidence: 84%
“…Patients with mild to moderate kidney disease often have low or undetectable circulating concentrations of 1,25(OH) 2 D (32–34). The major cause of 1,25(OH) 2 D deficiency is hyperphosphatemia, which can markedly reduce or completely shut down the renal production of 1,25(OH) 2 D (Fig.…”
Section: Renal Regulation Of 125(oh)2d3 Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperphosphatemia and secondary hyperparathyroidism (HPT) are common complications of end-stage renal disease (ESRD) (1). Untreated secondary HPT can lead to significant morbidity as a result of pain, pruritus, bone loss, increased fracture risk, and anemia (2,3) and can contribute to heart disease and hypertension (4,5).…”
mentioning
confidence: 99%
“…The effect of administered aluminium hydroxide on serum calcitonin was studied in non-dialysed patients with chronic renal failure by Takamoto et al [35]. Serum calcitonin did not change, whereas serum inorganic phosphate, and serum PTH fell.…”
Section: Discussionmentioning
confidence: 99%